2010
DOI: 10.1111/j.1752-1688.2009.00399.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Algaecides for Controlling the Density ofPrymnesium parvum1

Abstract: Prymnesium parvum has become more prevalent in water resources of the southern United States. As the potential impacts of P. parvum are relatively well known, especially its capability to severely affect fish, managers have sought efficacious, environmentally sound, and socially acceptable strategies for mitigating this noxious species. Laboratory testing was used to identify an effective algaecide for control of P. parvum from Texas, Arizona, Florida, North Carolina, and South Carolina. Cutrine Ò -Plus at 0.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…In addition to this study, Rodgers et al (2010) also found that copper-ethanolamine complex was more effective for controlling the problematic alga Prymnesium parvum at 10 3 -10 4 cells/mL than copper sulfate in laboratory studies. Importantly, copper concentration and formulation play important roles for controlling problematic algae.…”
Section: Comparative Toxicity Of Copper Compounds To Algaementioning
confidence: 80%
See 2 more Smart Citations
“…In addition to this study, Rodgers et al (2010) also found that copper-ethanolamine complex was more effective for controlling the problematic alga Prymnesium parvum at 10 3 -10 4 cells/mL than copper sulfate in laboratory studies. Importantly, copper concentration and formulation play important roles for controlling problematic algae.…”
Section: Comparative Toxicity Of Copper Compounds To Algaementioning
confidence: 80%
“…For example, noxious algae P. parvum has been related with fish kills in brackish inland waters (Lindholm et al, 1999;Roelke et al, 2010;Brooks et al, 2011;Umphres et al, 2012). Rodgers et al (2010) reported that the margin of safety for P. promelas and freshwater invertebrate Ceriodaphnia dubia after 96-h exposure to CutrinePlus required for controlling P. parvum was 4.3 and 0.6, respectively. Under this circumstance, authorities considering applications of copper formulations for controlling problematic algae will have to consider the relative risks of controlling problematic algae.…”
Section: Margins Of Safety For P Subcapitata At Different Cell Densimentioning
confidence: 97%
See 1 more Smart Citation
“…Since exposures of copper-based algaecides cause different responses by target algal species (Murray-Gulde et al, 2002;Rodgers et al, 2010;Bishop and Rodgers, 2012;Calomeni et al, 2014), laboratory predictions of responses of M. aeruginosa to exposures of copper-based algaecides can provide important information regarding the consequences of using copper-based algaecides for reliable and substantial reduction of M. aeruginosa blooms. Additionally, measurements of extracellular microcystin concentrations can indicate the post-treatment release of this endotoxin, and measurements of total microcystin concentrations are used to make risk-based decisions regarding the utilization of water resources.…”
Section: Introductionmentioning
confidence: 99%
“…Cell densities were determined using a Leitz Wetzlar Dialux 20 light microscope (Leitz USA Scopes, Paramount, California) and an Improved Neubauer Hemocytometer at 250x magnification (Rodgers et al, 2010). P. agardhii cell densities were estimated by counting the number of trichomes per 0.2 mm 2 gridded area on the hemocytometer and multiplied by the number of cells (12 cells) spanning this gridded area.…”
Section: Individual Algal Viability Measuresmentioning
confidence: 99%